CLINICAL ASSESSMENT OF THE EFFICIENCY OF THE APPLICATION OF THE IMPROVED TECHNIQUE OF MANUFACTURING PLASTIC BASES OF REMOVABLE DENTURES - O. A. Kryvchuk (Український стоматологічний альманах)
Complete removable dentures remain one of the most popular types of prosthetics in Ukraine. Despite this, their effectiveness remains insufficient, due to the poor influence of plate bases made of acrylic plastics.